Isu Lingkungan dalam Cerita Terdampar di Dunia Plastik: Implikasi Untuk Pembelajaran Bahasa Indonesia Responsif Lingkungan - Anisa Sofiana Perdani; Ari Ambarwati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this study is to describe the damage to nature illustrated in the story entitled Stranded in the Plastic World by Sukini. This research uses a literary ecology approach based on ecocritical theory. The method used is qualitative descriptive by analyzing the issue of environmental damage in the story Stranded in the Plastic World by Sukini. The result of his research is how environmental damage is described in the book. The damage includes damage to marine ecosystems, forests, and human life due to plastic waste which is already very troubling and dangerous. The implication of this research is the selection of teaching materials that respond to environmental damage for environmentally responsive Indonesian learning. The use of teaching materials containing environmental damage content to make students more involved in solving environmental damage that can be reached by students. This is a form of care, concern, and concern for the natural environment, which is also an educator to convey the dangers of plastic waste and the importance of protecting the environment and invites readers to become reliable change specialists in protecting the climate by reducing the use of single-use plastics such as straws, plastic sacks, and drinking water bottles. It also teaches children about the importance of protecting the environment and being responsible for our earth